Analisis Sistem Informasi Manajemen Mutu Berbasis Administrasi Akademik STIKES Persada Husada Indonesia - Diana Barsasella; Edi Junaidi (STIKes Persada Husada Indonesia, 2014)
Efforts to compensate for the increased demand of health human resources by increasing education system. Higher education is the next level study from secondary level where the resources should have the quality that can compete in the working world. Health education institutions can effectively help reduce the prevalence of health-risk behaviors among students and have a positive influence on students' academic performance. Quality of education contains three important components of quality outcomes, quality way or delivery process, and the special attraction or general institutional image, the third dimension can be translated into many dimensions of quality grain. BAN- PT accreditation of STIKES S1 PHI based on Department of Public Health Decree No. BAN-PT: 031/BAN-PT/Ak-XIV/S1/X/2011 received a grade of C with score of 250 (BAN-PT, 2011). Diploma of Nursing major has not been accredited by BAN-PT and only has accreditation from the Ministry of Health with grade of B. This is due to the quality management system has not been integrated where there is no data communication and coordination between unit, therefore the internal monitoring and evaluation (Monevin) is pacing slowly. The purpose of this study was to establish a quality management information system model (SIMM) based on academic administration. The study used a qualitative approach of SDLC development method with the RAD approach of system prototyping. The study was conducted in STIKES PHI that involve students, lecturers, STIKES Chairman, Academic Unit, Student Affairs Unit, Finance and Personnel Unit, Quality Assurance Unit. The result of this study consist of an analysis on problem input, process and output. Human resources, facilities and equipment, and inadequate information systems has contributed to the delays in quality management.